2017
DOI: 10.1371/journal.pone.0174604
|View full text |Cite
|
Sign up to set email alerts
|

Does shoe heel design influence ground reaction forces and knee moments during maximum lunges in elite and intermediate badminton players?

Abstract: BackgroundLunge is one frequently executed movement in badminton and involves a unique sagittal footstrike angle of more than 40 degrees at initial ground contact compared with other manoeuvres. This study examined if the shoe heel curvature design of a badminton shoe would influence shoe-ground kinematics, ground reaction forces, and knee moments during lunge.MethodsEleven elite and fifteen intermediate players performed five left-forward maximum lunge trials with Rounded Heel Shoe (RHS), Flattened Heel Shoe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 35 publications
0
39
0
Order By: Relevance
“…Reflective markers were placed over participants’ dominant leg according to a previous segment model [ 13 , 28 ]. After a standardized warm-up protocol including lower limb stretching exercises, participants familiarised themselves with the forward lunge step and tightened the lacings of the standard badminton shoes according to their individual preference for a badminton game.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Reflective markers were placed over participants’ dominant leg according to a previous segment model [ 13 , 28 ]. After a standardized warm-up protocol including lower limb stretching exercises, participants familiarised themselves with the forward lunge step and tightened the lacings of the standard badminton shoes according to their individual preference for a badminton game.…”
Section: Methodsmentioning
confidence: 99%
“…A spline interpolation was performed to rectify minor missing data using three frames of data before and after the missing data. The marker trajectories and GRF data were filtered with a fourth-order Butterworth bidirectional filter at 12 Hz and 100 Hz, respectively [ 13 , 28 ]. The cut-off frequencies were determined by the smallest difference between the estimated and true signal values [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chen and Zhu [40] analyzed on design of Lin Dan`s badminton shoes, suggested that special design in appearance, structure and processing technic were the biggest difference to compare with common badminton shoes. Recently, Lam et al [41], explored the in luence of shoe heel curvature on biomechanical parameters of lower extremities, result showed that shoe heel curvature played some role in variation of biomechanical parameters, and the difference in parameters may provide useful information for design of badminton shoes and prevention of injuries. This inding supported in luence results of badminton shoe heel on lower extremities by Li et al [15].…”
Section: The Design Of Badminton Shoesmentioning
confidence: 99%